1997
DOI: 10.1023/a:1026485622824
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cell death by apoptosis was analysed in HeLa cells either treated with the antitumoral drug bleomycin or depleted of growth factors by long-term culture without medium change. The interference of apoptosis with normal cell cycle progression was followed by flow cytometry in cells stained with propidium iodide and with antibody to S-phase-related PCNA protein. Bleomycin-treated cells showed a net accumulation in G2/M phase paralleled by the appearance of material with a subdiploid DNA content. Cells with a subd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[ 15 ] PCNA is not proliferation specific. [ 16 ] Many studies revealed a poor correlation between this antigen and other proliferation markers, in addition to clinical parameters. [ 17 ] Consequently, PCNA staining is no longer recommended for use in surgical pathology as it lacks all above mentioned advantages of Ki-67.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] PCNA is not proliferation specific. [ 16 ] Many studies revealed a poor correlation between this antigen and other proliferation markers, in addition to clinical parameters. [ 17 ] Consequently, PCNA staining is no longer recommended for use in surgical pathology as it lacks all above mentioned advantages of Ki-67.…”
Section: Introductionmentioning
confidence: 99%